Burn notice. Season four [videorecording (DVD)] - Campbell, Bruce, 1958-; Anwar, Gabrielle; Donovan, Jeffrey; Gless, Sharon (20th Century Fox Home Entertainment, 2011)
Master spy Michael Westen is back, and this time, he's joined by Jesse Porter, a no-nonsense counterintelligence expert who has been burned himself. Along with go-to guy Sam and the dangerously sexy Fiona, the team takes on a barrage of outlaw biker gangs, drug dealers, and a worldwide terrorist threat.